An atomically precise Ag18Cu8 nanocluster with rich alkynyl–metal coordination structures and unique SbF6− assembling modes. Issue 5 (13th January 2023) - Sun, Xueli; Tang, Xiongkai; Gao, Yan-Li; Zhao, Yujuan; Wu, Qingyuan; Cao, Dongxu; Shen, Hui
Abstract : [Ag18 Cu8 (dppp)4 ( t Bu-C6 H4 CC)22 ] 4+ clusters are self-assembled into a two-dimensional layer structure with the aid of SbF6 − anions. Quite rich coordination modes of alkynyl ligands and SbF6 − are observed. Abstract : Elucidating the coordination structures and assembling modes of atomically precise metal nanoclusters (NCs) remains a hot topic as it gives answers to the underlying mechanism of nanomaterials and bulk materials in terms of structure–property relationships. Here we report a novel silver–copper alloy NC featuring rich alkynyl–metal coordination modes and unique SbF6 − assembling structures. The NC, with the composition of [Ag18 Cu8 (dppp)4 ( t Bu-C6 H4 CC)22 ](SbF6 )4 (dppp = 1, 3-bis(diphenylphosphino)-propane), was prepared by a stepwise synthetic approach. Single-crystal X-ray diffraction analysis revealed that such a NC featured a staircase-like Ag18 Cu8 kernel, which was protected by hybrid alkynyl and dppp ligands in diverse coordination structures and multiple environments. The structural analysis also revealed the unique function of SbF6 − in inducing the assembly of cluster moieties, highlighting the importance of counterions in assembling nanomolecules. The diverse coordination structures of the protective ligands with metal ions and the indispensable roles of counterions in assembling the cluster moieties have also been supported by nuclear magnetic resonance (NMR) and electrospray ionization mass spectrometry (ESI-MS) studies, making it a model system to showcase the uniqueness of atomically precise metal NCs in illustrating the coordination chemistry of nanomaterials and bulk materials at the molecular level.